Pengaruh Serbuk Karet dari Ban Bekas sebagai Bahan Tambah Aspal Pen 60/70 pada Karakteristik Campuran Aspal Porus yang Menggunakan Agregat dari Loli Kota Palu - M. Mashuri (Civil Engineering Department, Tadulako University, 2022)
The use of waste crumb rubber tire as an additive in asphalt has been widely practiced in several countries in the world, which aims to improve the characteristics of asphalt mixtures such as porous asphalt. The purpose of this study was to determine the effect of used waste tire rubber powder as an additive in asphalt on the characteristics of porous asphalt mixture using aggregate from stone crusher machine in Loli, Palu city, Central Sulawesi Province. This research was conducted at the Transportation and Highway Laboratory, Tadulako University.This research used several percentages of used waste crumb rubber tire as follows: 0.025%, 0.050%, 0.075%, 0.10% of the aggregate weight in the mixtures (1200 grams). Aggregate composition determination in mixture using Method by sieve. Optimum Asphalt Content determination using Marshall Method. The results of this research found that the Stability and density value of the mixtures tend to increase at the content of 0.025% - 0,075% used waste crumb rubber tire. The results also found that the maximum stability and maximum density were reached at the Optimum Asphalt Content and the used waste crumb rubber tires content were 0.58% and 0.075%.